Distributed, Cloud, and Fog Computing Motivations on Improving Security and Privacy of Internet of Things - Teba Mohammed Ghazi Sami, Zainab Salih Ageed, Zryan Najat Rashid, Yousif Sufyan Jghef (Mathematical Statistician and Engineering Applications, 2022)
In spite of the benefits afforded by wireless communications networks, maintaining the confidentiality and safety of wireless networks remains a significant obstacle and source of worry. The principal uses of wireless communication networks are found in the military, commercial, retail, transportation, healthcare, and many other fields; these systems utilise wired, cellular, or ad hoc networks. Other applications of wireless communication networks include: In recent years, a substantial amount of research attention has been focused on the Internet of Things (IoT). Looking forward, the IoT will play an important role and will affect our lives as well as the standards and business models that we now use. It is anticipated that the usage of IoT in a variety of applications would significantly rise during the next several years. The Internet of Things makes it possible for billions of different individuals, equipment, and services to connect with one another and share information. IoT networks are becoming more vulnerable to a wide variety of security threats as their usage continues to grow. In order to provide identification, secrecy, access control, and integrity, among other things, effective security and privacy protocols are an absolute need for Internet of Things (IoT) networks. This article presents a research that is both extensive and comprehensive on the topic of privacy and security in IoT.